PHYSICAL EXERCISE TECHNIQUES: PHYSICAL EXERCISE TECHNIQUES - ismatov, abduqodir (Физическое воспитание, спорт и здоровье, 2022)
This article provides an overview of exercise theory based on pedagogical tasks and provides feedback on the teacher’s options for choosing the most effective exercise.